TERAPIA COMUNITÁRIA NA SAÚDE MENTAL DO PACIENTE IDOSO - Nogueira Gonçalves, Sara Maria; Lima da Silva, Renata Amanda; Viana Oliveira, Lina Clenes; Abreu da Silva, Francisca Jéssica; da Silva Feitosa, Andreza Ravena (SANARE - Revista de Políticas Públicas, 2015)
-